Media Pembelajaran Poster Berbasis Aplikasi Android Dengan Pendekatan Kontekstual Pada Materi Termodinamika - Arum Wulandari; Hadi Nasbey; Yetti Supriyati (Risenologi, 2021)
People are required to be able to make changes in their activities using technology, information, and communication. One of the factors that influence learning activities is the selection of interesting learning media. This research aims to develop poster learning media based on Android applications. Based on the report of the national exam results in 2019 the Ministry of Education and Culture that the mastery of the lowest material on thermodynamics with the percentage of students who answered correctly amounted to 28.58 out of 100 and the analysis of the needs of students at SMAN 99 Jakarta with 80 respondents resulted in that 73.8% of students still do not understand the working principle of Carnot machines. The result was caused by the delivery of material with a percentage result of 61.3% of students answering the delivery of material that is still monotonous. This research and development refer to the Dick &Carey model. This product has gone through the media expert test stage with a feasibility percentage of 88.42%, a material expert test obtained a feasibility percentage of 89.53%, and a learning expert test with a feasibility percentage of 80%. Conducted trials to students with a feasibility percentage of 89.5% and trials to teachers with a feasibility percentage of 97%. The results of this study show that poster learning media based on android applications with the contextual approach to thermodynamic materials deserves to be used in learning.